Functional, compositional, and regulatory analyses of imported and non‐imported single dental crowns. (17th August 2020) - Valen, Håkon; Staxrud, Frode; Kopperud, Simen E.; Austrheim, Ellen; Syverud, Morten; Mulic, Aida
Abstract : The aims of the study were to investigate functional and esthetic properties, the composition of the alloy, and the content of hazardous elements of single dental crowns with metal skeleton and fired porcelain. Epoxy models made from full mouth impressions taken of a patient with a crown preparation of the right maxillary first permanent molar were used for production of identical polyether impressions, which were distributed to dentists in Norway. The dentists sent the impressions to their regular dental laboratories. All 55 crowns collected were anonymized and examined. Of the crowns received, 35 were made in Norway, 12 were imported, and 8 were of unknown origin. The evaluation of functional properties revealed that 50% of the Norwegian, 42% of the imported, and 25% of the unknown‐origin crowns were considered unacceptable. The composition of the alloy was not in accordance with that stated by the manufacturer for 17%, 13% and 20% of the crowns, where this information was provided. The lead content of the alloy exceeded the limit set by the ISO 22674: 2016 for 18% of the crowns in total. The statement that shall follow the work according to EU‐regulations was not complete for approximately 75% of the works received.